Positive and negative features of psychopathological symptoms at atypical variants of simple-type schizophrenia - A. V. Moseyko (Kazimierz Wielki University, 2017)
The objective: to establish features of psychopathological structure atypical course of schizophrenia simple form. The research was done on the  base of «RegionalClinicalPsychiatric Hospital» (Zaporozhye). 100 patients with simple schizophrenia were examined. Rating scale of general psychopathology (PSS and NSS, S. R. Kay, L. A. Opler, A. Fiszbein, 1987) was used. It has been revealed that for the patients with 0 level atypia clinical symptoms are characterized by low levels of positive and significant severity of negative psychopathological phenomena, such as blunted affect, difficulty of abstract thinking, emotional and apathetic social withdrawal; for the patients with level 1 atypia  high rates of excitement, hostility and poor rapport were typical; patients with 2 level of atypia had persecution and stereotyped thinking; patients with 3 levels atypia developed delusion, conceptual disorganization, persecution and difficulty of abstract thinking.